Academic Information Service Chatbot Using HMM and AIML - Affandes, Muhammad; Pizaini, Pizaini (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
UIN Suska Riau campus led to an escalation amount of data and information that must be maintained, such as academic information. UIN Suska Riau is responsible for managing and providing academic information to students and other academic communities. We can ask the Customer Care Center (C3) in Academic System or come directly to the PTIPD UIN Suska Riau office for academic questions. There still has limitations to serving existing questions submitted through C3 because officers can only serve during working hours both online and offline. Chatbots can be used to support the work of C3 officers in serving the questions asked. This system is built based on Named Entity Recognition (NER) using Artificial Intelligence Markup Language (AIML). We perform NER analysis using HMM. This study uses the contents of the academic manual as a base knowledge with 150 categories of questions and 30 answers that produce an accuracy of 55%.